THE ROLE OF CITY’S BRAND EQUITY’S DIMENSION ON TOURIST’S VISIT INTENTION USING FAMILIARITY AS MEDIATION: A STUDY OF TANGERANG CITY INDONESIA - Antony Stevanus Purba; Maria Dini Gilang Prathivi; Ririsma Sihombing (Institute of Research and Community Outreach - Petra Christian University, 2023)
The purpose of this study is to determine the extent to which brand equity influences visitor interest to visit Tangerang city as one of the tourism destinations. The majority of empirical studies have proposed that brand recognition and familiarity with a tourist destination city (familiarity) has a positive correlation with the tourist destination's image. This research is to determine how much influence brand equity has using the dimension of brand quality, brand image, brand loyalty, and brand awareness as familiarity used as mediating variable.